Return to relevance. Issue 1 (9th February 2015) - Fox, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In order to continue to respond to patron needs in a relevant way, it is necessary to continuously reevaluate the central message that the library website is intended to convey. It's necessary to question assumptions, listen to user needs, and shift our paradigm to make the library web presence as effective as possible. Design/methodology/approach – This is a regular viewpoint column. A basic literature review was done prior to the column being written. Findings – The library Web site remains, in many respects, the "first face" of the library for patrons. To remain relevant, traditional methodologies used in library science may need to be set aside or catered to the needs of the patron. Originality/value – Various methods regarding design philosophy are explored which may be of use to information professionals responsible for the design and content of the library Web sites.